Analisis Program Makan Siang Gratis terkait Implementasi, Respon Masyarakat, dan Tantangan Pelaksanaan - Pat Kurniati; Rizky Bintang Setiawan; Tias Sil Romansyah; Muhammad Rizal Fahmi; Matang (CV. Kurnia Grup, 2026)
This literature study aims to analyze the Free Lunch Program (MBG) in Indonesia, one of the campaign promises of the President-elect. MBG is one of the flagship programs of Mr. Prabowo Subianto. Nearing one year into his administration, the program's implementation, public response, and challenges are being investigated. This research is based on a review of 150 articles obtained through Google Scholar, with 53 selected journal articles subjected to in-depth analysis. The study results indicate that the implementation of the MBG program has an impact on improving student nutrition, attendance, and academic achievement. The program contributes to food security and human resource development. Public responses are quite diverse, ranging from positive sentiment supporting the program's objectives to criticism of potential budget misuse and program effectiveness. Media framing also contributes to shaping public perception of the MBG program. Challenges to program implementation include budgeting, cross-sector coordination, and program sustainability after five years in office. This study recommends that further studies examine the effectiveness of the MBG program through a quantitative approach based on field data, given the limited research related to evaluating the impact of this policy.